Faktor – Faktor Yang Mempengaruhi Persepsi Terhadap Kepatuhan Wajib Pajak - Herlina, Herlina; Putra, Rio Johan (Politeknik Ganesha Medan, 2024)
This research aims to examine the influence of various factors, including perceptions of tax corruption, perceptions of justice, social influences and norms, legal and ethical awareness, as well as education and knowledge, on taxpayer compliance. The sample in this research was